Oral Health-Related Knowledge, Attitudes, and Practices of Diabetic Patients in Tanzania - Karpal Singh Sohal; Ramadhani Kambole; Sira Stanslaus Owibingire (International Dental Journal)
Aim: To assess oral health-related knowledge, attitude, and practices (KAP) of patients with diabetes mellitus (DM) attending public diabetic clinics in Dar es Salaam, Tanzania. Methodology: This study involved adult patients diagnosed with DM. A questionnaire with questions related to oral health KAP was used. Data analysis was done using SPSS software v26. Multivariate regression analysis was utilized for response analysis. An alpha of less than 0.05 was considered to indicate statistical significance. Results: Participants with good levels of KAP related to oral health comprised 51.0%, 82.3%, and 20.6%, respectively. The odds of good oral health knowledge among participants were almost 2 folds higher in participants with high education levels and 7 folds higher in those who had been referred to a dentist by a physician. Participants with good oral health knowledge had 5.5 times higher odds of having a good attitude. The participants with high education levels were almost 3 times more likely to have good practice. Conclusion: About half of the patients with DM have good oral health-related knowledge. A majority have good compliance towards oral health, but only a limited number have good oral health-related practices. The level of education and previous referrals to dental professionals were found to be predictors of good knowledge regarding dental health.